As animações iluminando o conhecimento - Rosado, Diogo Gregório (2020)
This dissertation is of a qualitative nature and uses the short films of Pixar Animation Studios in education and as a general aim to explain whether these short films are pedagogical tools that help build knowledge in the classroom. From this assumption we try to get to know the pedagogical practice of teachers who use these resources in the classroom, as well as analyze whether these works bring elements that help to reflect on the reality of the student and, finally, confirm whether the short films are important in building knowledge. The research used the theoretical references based on Projection-Identification-Transference and thoughts on aesthetics involving Paulo Freire and Edgar Morin. Furthermore, field research was also undertaken through structured interviews with teachers. Based on the analysis and interpretation of th e data collected, it could be concluded that short films do contribute to the building of knowledge and learning in the classroom. The results indicated that the showing of films culminated in activities, in which the students gave thought to the themes presented in the cinematographic works and produced new works from the short films. The educators recognize the importance of working with the films. This study, therefore, highlights the potential that can be gained from the use of animated films in the classroom in broadening dialogues in the building of knowledge.